2015
DOI: 10.1080/00140139.2015.1066877
|View full text |Cite
|
Sign up to set email alerts
|

Impact of noise on self-rated job satisfaction and health in open-plan offices: a structural equation modelling approach

Abstract: This study uses a structural equation model to examine the effects of noise on self-rated job satisfaction and health in open-plan offices. A total of 334 employees from six open-plan offices in China and Korea completed a questionnaire survey. The questionnaire included questions assessing noise disturbances and speech privacy, as well as job satisfaction and health. The results indicated that noise disturbance affected self-rated health. Contrary to popular expectation, the relationship between noise disturb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
57
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(62 citation statements)
references
References 57 publications
4
57
0
1
Order By: Relevance
“…The problems experienced in open-plan offices have been widely documented in the literature (e.g., Bodin Danielsson & Bodin, 2008;De Croon, Sluiter, Kuijer & Frings-Dresen, 2005;Haapakangas, Helenius, Keskinen & Hongisto, 2008;Kim & de Dear, 2013;Lee, Lee, Jeon, Zhang & Kang, 2016;Pejtersen, Allermann, Kristensen & Poulsen, 2006). Open-plan offices are associated with various environmental complaints, particularly noise and lack of privacy (Bodin Danielsson & Bodin, 2009;Brookes & Kaplan, 1972;De Croon et al, 2005;Pejtersen et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The problems experienced in open-plan offices have been widely documented in the literature (e.g., Bodin Danielsson & Bodin, 2008;De Croon, Sluiter, Kuijer & Frings-Dresen, 2005;Haapakangas, Helenius, Keskinen & Hongisto, 2008;Kim & de Dear, 2013;Lee, Lee, Jeon, Zhang & Kang, 2016;Pejtersen, Allermann, Kristensen & Poulsen, 2006). Open-plan offices are associated with various environmental complaints, particularly noise and lack of privacy (Bodin Danielsson & Bodin, 2009;Brookes & Kaplan, 1972;De Croon et al, 2005;Pejtersen et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The role of distractions in other problems has been explored in a few field studies. The studies examining structural equation or mediation models have linked distraction-related variables to job satisfaction (Veitch, Charles, Farley & Newsham, 2007), self-rated health (Lee et al, 2016) and emotional exhaustion (Herbig et al 2016;Laurence, Fried, & Slowik, 2013). However, all of these studies have been restricted to cross-sectional data.…”
mentioning
confidence: 99%
“…• Visual comfort, access to daylight, and view [19][20][21]; • Noise distraction, lack of privacy, and communication [22][23][24][25][26][27]; • Office design [28][29][30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%
“…Hongisto et al [54] denoted that it is not the sound level of noise, but the intelligibility of irrelevant background noise that determines the distracting power of speech. In addition, Lee et al [25] found that some of the workers who have high noise-sensitivity could be adversely affected by open-plan office arrangement, due to loss of speech privacy.…”
Section: Introductionmentioning
confidence: 99%
“…The traditional view of research of the open-plan design held that this type of design would facilitate more interaction and collaboration between employees, thereby contributing to increased productivity and performance [6][7][8]. However, a recent trend of research has started associating open-plan office design with negative outcomes such as increased sick leave; higher levels of stress, distraction and disturbance; as well as reduced job satisfaction and performance [9][10][11][12][13]. The underlying argument among most of these studies has been the effects of noise and distraction.…”
Section: Introductionmentioning
confidence: 99%